2022
DOI: 10.1007/s00406-022-01413-9
|View full text |Cite
|
Sign up to set email alerts
|

Diminished capacity to make treatment decision for COVID-19 vaccination in schizophrenia

Abstract: Recent evidence suggests that people with schizophrenia are at high risk for severe COVID-19 and should be prioritized for vaccination. However, impaired decision-making capacities could negatively affect the uptake of COVID-19 vaccination in this population. Capacity to consent to COVID-19 vaccination was assessed in 80 outpatients with schizophrenia. Using the MacArthur Competence Assessment Tool for Treatment, 56.3% of the sample were classified as having diminished capacity to consent to the vaccination. D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Recently and within the context of the COVID-19 pandemic, two large-scale studies have shown that both conspiracy beliefs and persecutory ideas, two psychological features that are highly present in individuals with schizophrenia, were positively associated with COVID-19 vaccine hesitancy and resistance in the general population [15,16]. Finally, our research team recently showed that impaired competence to consent to a COVID-19 vaccine was associated with lower vaccination rates in people with schizophrenia [17].…”
Section: Introductionmentioning
confidence: 86%
“…Recently and within the context of the COVID-19 pandemic, two large-scale studies have shown that both conspiracy beliefs and persecutory ideas, two psychological features that are highly present in individuals with schizophrenia, were positively associated with COVID-19 vaccine hesitancy and resistance in the general population [15,16]. Finally, our research team recently showed that impaired competence to consent to a COVID-19 vaccine was associated with lower vaccination rates in people with schizophrenia [17].…”
Section: Introductionmentioning
confidence: 86%
“…Of potential note here, patients believing COVID-19 conspiracy theories may be more prone to contracting the virus, which may itself be a risk factor for developing psychosis [ 64 ]. Interestingly, a recent study by Raffard et al demonstrated that patients with schizophrenia have diminished capacity to consent to COVID-19 vaccination [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unwillingness to vaccine has been associated with greater psychiatric symptoms in patients with schizophrenia: symptomatic patients with schizophrenia frequently are suspicious of the Government for wanting to vaccinate people and develop paranoid delusions around the vaccination itself and the process [55][56][57]. However, this suspicion was not limited to patients with psychotic disorders and younger age, lower education and economic status, right-wing and conservative ideology have been associated with increased belief in misinformation [58].…”
Section: Vaccination Policies Unwillingness To Vaccine and Rates Of V...mentioning
confidence: 99%